Zero-lactose sherbet with honey: Sensory analysis and economic viability - GARCIA, Lismaíra Gonçalves Caixeta; PERES, Daiane Sousa; MARQUES, Rubia Cristina Arantes; OLIVEIRA FILHO, Josemar Gonçalves de; EGEA, Mariana Buranelo; dos SANTOS, Priscila Alonso (Food Science and Technology, 2024)
The objective of this study was to develop a zero-lactose sherbet sweetened with honey by means of sensory analysis and to calculate its economic viability. Using a simplex-centroid mix design, nine mixes were prepared. Microbiological analyses were performed to ensure the safety of the judges in the sensory analysis. The sensory analysis was performed in two stages: the order-preference test of the formulations obtained in the experimental design and the affective acceptance test of the most preferred sample in the order-preference test. The acceptability index was also used. The economic viability was calculated by comparing its cost with the cost of the standard sherbet formulation. In the order-preference test, the sample with 13.80 g/100 g honey, 2.25 g/100 g emulsifier, and 0.85 g/100 g neutral alloy was the most preferred. In the affective test, all the attributes had an acceptability index greater than 80%, classifying the ice cream as having good sensory acceptance since it is necessary for the index to be above 70%. The zero-lactose sherbet sweetened with honey costs 40% more than the traditional sherbet. Therefore, we can conclude that the development of zero-lactose ice cream sweetened with honey is a product sensorial and accepted by consumers. Despite the cost of production, consumers prefer healthier products even if they have to pay a higher price.